Balloon measurements of aerosol in the Antarctic stratosphere - Morita, Y.; Takagi, M.; Iwasaka, Y.; Ono, A. (1985)
Three balloon soundings of aerosol were conducted from Syowa Station, Antarctica in April, June and October 1983. Number concentration and the size distribution of aerosol particles with diameter greater than 0.3 microns were measured by using a light scattering aerosol particle counter. The influence of the eruption of Mt. El Chichon on the aerosol concentration in the stratosphere was observed on October 16. Very high aerosol concentration at stratospheric heights was obtained from the first successful aerosol sounding in winter Antarctic stratosphere. The result gives direct evidence of winter enhancement in the Antarctic stratosphere.